Fan Mussel (Pinna nobilis L.) Spat Collection, Monitoring of Early Growth and Conservation Implications by Deploying Conventional Aquaculture Methodology - John A. Theodorou; Efthimios Spinos; Alexis Ramfos; Ioannis E. Tsamadias; Vlasoula Bekiari; Maria Kamilari; Maria-Myrto Ntouni; Dimitrios Tsotsios; Konstantinos Feidantsis; Athanasios Lattos; Ioannis A. Giantsis; Basile Michaelidis (Journal of Marine Science and Engineering, 2024)
Pinna nobilis, endemic to the Mediterranean Sea, has been experiencing a gradual population decline over recent decades due to anthropogenic pressures on its ecosystems. However, since 2016, its populations have suffered significant reductions because of pathological issues affecting the species across all its habitats. Aquaculture techniques to support the limited natural recruitment P. nobilis efforts is examined. Artificial substrates for larval attachments in aquaculture infrastructures promote the survival of the juveniles that is further enhanced through protected pre-growing “nursery” farming conditions. Specific spat collectors were placed in 2 cage-fish farms in SW Amvrakikos Gulf. The harvested spats from were transferred to pre-grow in trays hanged on a long line farm mussel that is acting as a protected “nursery”, avoiding predation and any human accidentally disturbance. The survival and growth of 12 juveniles P. nobilis spat (shell length 38.1 ± 9.2 mm) in captivity (31 October 2023–15 March2023) was investigated. Out of the 12 individuals collected, 3 were examined for the presence of pathogens; only 7 survived, exhibiting enhanced growth (shell length 54.3 ± 11.6 mm) after 134 days in the nursery. The results highlight the significant role of aquaculture techniques in efforts to conserve a threatened species as well as the need for the creation of a protocol to ensure the conservation of P. nobilis.